2015
DOI: 10.1002/adhm.201400798
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Materials for Self‐Renewal, Long‐Term Maintenance, and Differentiation of Induced Pluripotent Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) have attracted considerable attention from the public, clinicians, and scientists since their discovery in 2006, and raised huge expectations for regenerative medicine. One of the distinctive features of iPSCs is their propensity to differentiate into the cells of three germ lines in vitro and in vivo. The human iPSCs can be used to study the mechanisms underlying a disease and to monitor the disease progression, for testing drugs in vitro, and for cell therapy, avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 95 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…In 2010, three separate research groups identified fully defined engineered matrix compositions that permitted feeder-free expansion of ESCs: recombinant laminin 511 (100), acrylate surfaces presenting RGD peptides (101), and synthetic poly[2-(methacryloyloxy)ethyl dimethyl-(3-sulfopropyl)ammonium hydroxide] (PMEDSAH) grafted surfaces (102). Since these reports, various other naturally derived and synthetic materials have been developed to support the culture of undifferentiated PSCs (103). In addition to controlling surface biochemistry, biophysical interactions with the substrate must also be considered.…”
Section: Stem Cell Expansionmentioning
confidence: 99%
“…In 2010, three separate research groups identified fully defined engineered matrix compositions that permitted feeder-free expansion of ESCs: recombinant laminin 511 (100), acrylate surfaces presenting RGD peptides (101), and synthetic poly[2-(methacryloyloxy)ethyl dimethyl-(3-sulfopropyl)ammonium hydroxide] (PMEDSAH) grafted surfaces (102). Since these reports, various other naturally derived and synthetic materials have been developed to support the culture of undifferentiated PSCs (103). In addition to controlling surface biochemistry, biophysical interactions with the substrate must also be considered.…”
Section: Stem Cell Expansionmentioning
confidence: 99%
“…These hydrogels have been shown to encapsulate iPSCs well enough for injecting into structures with desired architectures, sustaining stem cell pluripotency, and supporting differentiation in 3D 16 . These biomaterials were all found to support spatial distribution and to promote the expansion and maturation of iPSC populations in long-term cultures for up to 3–4 months 1719 . In addition, combinations of these materials have viscoelastic properties that allow rapid prototyping via the inkjet printing of defined architectural constructs 16, 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Porous scaffolds and hydrogels are also amenable to the development of patient-specific regenerative treatment sutilizing the potential of induced pluri potent stem cells (iPSCs). 122 Advances on all three fronts of tissue engineering – material matrix design, drug delivery, and regenerative cells – will help to push the field into clinical use in the near future.…”
Section: Discussionmentioning
confidence: 99%